Topographical and depth-dependent glycosaminoglycan concentration in canine medial tibial cartilage 3 weeks after anterior cruciate ligament transection surgery—a microscopic imaging study - Mittelstaedt, Daniel; Kahn, David; Xia, Yang (Quantitative Imaging in Medicine and Surgery, 2016)
Background: Medical imaging has become an invaluable tool to diagnose damage to cartilage. Depletion of glycosaminoglycans (GAG) has been shown to be one of the early signs of cartilage degradation. In order to investigate the topographical changes in GAG concentration caused by the anterior cruciate ligament transection (ACLT) surgery in a canine model, microscopic magnetic resonance imaging (µMRI) and microscopic computed tomography (µCT) were used to measure the GAG concentration with correlation from a biochemical assay, inductively coupled plasma optical emission spectroscopy (ICP-OES), to understand where the topographical and depth-dependent changes in the GAG concentration occur. Methods: This study used eight knee joints from four canines, which were examined 3 weeks after ACLT surgery. From right (n=3) and left (n=1) medial tibias of the ACLT and the contralateral side, two ex vivo specimens from each of four locations (interior, central, exterior and posterior) were imaged before and after equilibration in contrast agents. The cartilage blocks imaged using µMRI were approximately 3 mm × 5 mm and were imaged before and after eight hours submersion in a gadolinium (Gd) contrast agent with an in-plane pixel resolution of 17.6 μm2 and an image slice thickness of 1 mm. The cartilage blocks imaged using µCT were approximately 2 mm × 1 mm and were imaged before and after 24 hours submersed in ioxaglate with an isotropic voxel resolution of 13.4 µm3. ICP-OES was used to quantify the bulk GAG at each topographical location. Results: The pre-contrast µMRI and µCT results did not demonstrate significant differences in GAG between the ACLT and contralateral cartilage at all topographical locations. The post-contrast µMRI and µCT results demonstrated topographically similar significant differences in GAG concentrations between the ACLT and contralateral tibia. Using µMRI, the GAG concentrations (mg/mL) were measured for the ACLT and contralateral respectively, the exterior (54.0±3.6; 70.4±4.3; P=0.001) and interior (54.9±5.9; 71.0±5.9; P=0.029) demonstrated significant differences, but not for the central (61.0±12.0; 67.4±7.2; P=0.438) or posterior (61.6±6.3; 70.3±4.4; P=0.097) locations. Using µCT, the GAG concentrations (mg/mL) were measured for the ACLT and contralateral respectively, the exterior (68.8±0.4; 87.7±4.1; P=0.023) and interior (60.5±9.1; 82.6±8.7; P=0.039) demonstrated significant differences, but not for the central (53.5±5.5; 59.1±25.6; P=0.684) or posterior (52.3±6.2; 61.5±12.7; P=0.325) locations. The depth-dependent GAG (mg/mL) profiles showed significant differences in µMRI for the transitional zone (TZ) [exterior (28.1±4.7; 47.0±8.6; P=0.01) and interior (32.6±4.8; 43.8±8.7; P=0.025)], radial zone (RZ) 1 [exterior (49.6±4.8; 71.5±5.8; P=0.001) and interior (49.4±7.4; 66.7±6.8; P=0.041)], and RZ 2 [exterior (74.9±4.7; 91.8±2.9; P=0.001) and interior (77.1±6.0; 94.8±4.5; P=0.015)], and in µCT for the superficial zone (SZ) [interior (20.6±1.2; 40.4±5.4; P=0.004)], TZ [exterior (45.6±12.0; 61.8±0.5; P=0.049) and interior (36.3±11.7; 60.8±2.0; P=0.019)], and RZ 1 [exterior (61.1±4.1; 85.3±5.6; P=0.039) and interior (53.9±4.9; 78.0±5.1; P=0.041)] for the ACLT and contralateral, respectively. ICP-OES measured significant differences in GAG were found for the exterior (42.1±19.6; 65.3±16.2; P=0.017), central (43.4±4.4; 65.3±10.6; P=0.0111), and interior (46.8±5.6; 61.7±7.3; P=0.0445) but not for the posterior (52.6±12.1; 59.0±2.6; P=0.9252) medial tibia locations compared for the ACLT and contralateral, respectively. Conclusions: The detection and correlation between the three techniques show a topographic depth-dependency on the initial GAG loss in injured cartilage. This topographic and high resolution investigation of ACLT cartilage demonstrated the potential of using µMRI and µCT to study and help diagnose cartilage with very early stages of osteoarthritis.